Rancang Bangun Aplikasi Dashboard Laporan Pengaduan Kendala Sistem Internal pada PT. Telkom Indonesia Witel Purwokerto berbasis Website menggunakan Metode Prototype - Fahrezi, Raihan Ahmad; Prasetyo, Novian Adi (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The development of Internet technology has increased the number of internet users and affected people's lives at large. As a telecommunications company, PT. Telkom Indonesia Tbk. (Telkom) provides Indihome services, has an increasing number of customers. To meet customer needs, Telkom gave responsibility to the Access Service Operation (ASO) unit at Witel Purwokerto to supervise and control Indihome services. However, the recording of complaints by the Access Service Operation (ASO) unit is still done manually, resulting in duplicate orders and recording imperfections. Based on the existing problems, the author designed a complaint report system that uses methods such as the System Development Life Cycle (SDLC) Prototype model to overcome these problems and uses black box and white box testing methods. The purpose of this study is to build a system that will facilitate Witel Purwokerto's Access Service Operation (ASO) unit in accommodating data on complaint reports made by whistleblowers. The system is built using PHP programming language with the help of Laravel framework, and as database management using MySQL. The test results of the system with the black box and white box methods showed 99.74% success for black box testing, and the white box test results showed 100% success. It can be concluded that every function on the dashboard website reports complaints of internal system constraints in this study runs well.